The Role of Investments in the Development of the Real Sector (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article explores the impact of investments on the development of Uzbekistan's real sector, addressing key challenges such as infrastructural deficits, regulatory complexities, and skill shortages. It proposes solutions like public-private partnerships, regulatory reforms, and human capital development to enhance investment efficacy. The recommendations aim to foster a dynamic real sector, crucial for Uzbekistan's sustainable economic growth.